Effect of pH, Temperature, Dissolved Oxygen, and Flow Rate of Overlying Water on Heavy Metals Release from Storm Sewer Sediments. (2nd December 2013) - Li, Haiyan; Shi, Anbang; Li, Mingyi; Zhang, Xiaoran
Abstract : The concentrations and the amount of cumulative release of heavy metals (Zn, Cu, Cd, Cr, and Pb) in contaminated sediments collected from combined sewer system were investigated in order to provide a complete overview of the key variables affecting the heavy metals release from storm sewer sediments. The heavy metals release rates were affected to a much greater extent in the low pH (4–7) condition than in high pH (8–10) condition. At higher temperature (30–35°C) the release rates of metals were increased more rapidly than at low temperature. The release of Zn, Cu, Cr, and Pb appeared to increase under the aerobic condition during the first 150 min and then the concentration kept stable. Moreover, the adsorption of these metals and the release of Cd occurred in the anaerobic condition. The flow rate significantly affected the release amount of Zn, Pb, and Cr, while it slightly affected the concentration of Cu and Cd. This study reflects that any change of pH, temperature, dissolved oxygen, and flow rate of overlying water all cause the different variations of the concentrations of heavy metals.